VECTOR-MESON PRODUCTION IN THE FINAL-STATE K+K-PI+PI- OF PHOTON-PHOTON COLLISIONS - Althoff, M; Braunschweig, W; Gerhards, R; Kirschfink, J; Martyn, H; Rosskamp, P; Wallraff, W; Bock, B; Eisenmann, J; Fischer, H; Hartmann, H; Jocksch, A; et al. (Springer-Verlag, 1986)
Vector meson production is studied in the reaction γγ→K+K-π+π-. A clear Φ(1020) signal is seen in the K+K- mass distribution and a K*0 (890) signal is visible in the K±π∓ one. Both do not seem to be strongly correlated with quasi two body final states. Cross sections for the processes γγ→K+K-π+π-, γγ→Φπ+π-, γγ→K+0K±π∓ and upper limits for the production of Φp, ΦΦ and K*0 Mathematical expression are given as function of the invariant γγ mass. © 1986 Springer-Verlag.